Blocking muscarinic receptors in the olfactory bulb impairs performance on an olfactory short-term memory task - Devore, Sasha; Manella, Laura C.; Linster, Christiane (Frontiers in Behavioral Neuroscience, 2012)
Cholinergic inputs to cortical processing networks have long been associated with attentional and top-down processing. Experimental and theoretical studies suggest that cholinergic inputs to the main olfactory bulb (OB) can modulate both neural and behavioral odor discrimination. Previous experiments from our laboratory and others demonstrate that blockade of nicotinic receptors directly impairs olfactory discrimination, whereas blockade of muscarinic receptors only measurably impairs olfactory perception when task demands are made more challenging, such as when very low-concentration odors are used or rats are required to maintain sensory memory over long durations. To further investigate the role of muscarinic signaling in the OB, we developed an olfactory delayed match-to-sample task using a digging-based behavioral paradigm. We find that rats are able to maintain robust short-term odor memory for tens to hundreds of seconds. To investigate the role of muscarinic signaling in task performance, we bilaterally infused scopolamine into the OB. We find that high dosages of scopolamine (38 mM) impair performance on the task across all delays tested, including the baseline condition with no delay, whereas lower dosages (7.6 mM and 22.8 mM) had no measureable effects. These results indicate that general execution of the match-to-sample task, even with no delay, is at least partially dependent on muscarinic signaling in the OB.